Analysis of Nurses' Caring Behavior Based on Watson's Theory related to the Anxiety of Chronic Kidney Disease Patients - Wati, Nurahma; Anjaswarni, Tri; Ernawati, Naya; Nataliswati, Tri (Jambura Nursing Journal, 2026)
Nurse caring behavior is a nurse's action based on empathy, compassion, skills and responsibility that has benefits for patient recovery. Lack of nurse caring behavior can cause psychosocial problems (anxiety) during treatment and certain medical procedures. The purpose of this study was to analyze nurse caring behavior based on Watson's theory in relation to the level of anxiety in chronic kidney disease patients undergoing hemodialysis. The research method was observational with a cross-sectional design. The population of all chronic kidney disease patients undergoing hemodialysis at Kanjuruhan Hospital was 313 patients. The sample was taken using a purposive sampling technique with a sample size of 75 patients based on the Slovin formula calculation. The instrument used the nurse caring behavior questionnaire (KPCP) and the Hospital Anxiety and Depression Scale (HADS Anxiety). Data analysis used the Spearman rank correlation hypothesis test. The results show that the caring behavior of nurses based on Watson's theory is sufficient, the level of anxiety of patients with chronic kidney disease is mild, the value (p = 0.000